Laporan Kasus: Ekstraksi Gigi dengan Perubahan Matriks Tulang sebagai Persiapan Pembuatan Gigi Tiruan Lengkap - Fadhila Nurin Shabrina; Bambang Tri Hartomo (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2021)
Patients in the elderly group have a higher risk for dental and oral health problems because in old age, caries and periodontal tissue are generally more severe and progressive. The aging process causes changes in the structure and appearance of the teeth, the oral mucosa, the decline in function salivary glands, and loss of bone minerals through bone matrix resorption. The occurrence of bone matrix resorption results in the elderly group more often experiencing tooth loss which can be exacerbated by the occurrence of periodontal disease. After tooth extraction, this condition needs to be considered by dentist so that the denture made later has good retention and stabilization and remains comfortable for the patient to use. The aim was providing an overview regarding the procedure of extraction teeth with the change of bone matrix as a preparation for the prosthodontic complete dentures treatment. A 56-year-old female patient came to RSGM Unsoed wanted to order complete dentures so that the remaining teeth shoul be extracted. Patient feels discomfort and difficulties when eating and drinking. Intraoral examination, only teeth 16 were left with gingival recession. The patient's alveolar bone condition showst ends to be flat in the edentulous posterior area. The extraction case in elderly patients must be carried out according to the right procedure with minimal trauma so as not to damage the supporting tissue around the tooth and facilitate the process of denture treatment.